Evaluating the test-retest reliability of the SLUMP questionnaire for measuring biomechanical issues during laptop use among university students. - D'Silva, Chelsea; Côté, Pierre; Murphy, Bernadette; Barakat-Haddad, Caroline (Work, 2018)
BACKGROUND: Laptop use may be associated with poor health among University students. However, no psychometrically-sound instrument is available to measure biomechanical issues during laptop computer use in this population. OBJECTIVE: To evaluate the test-retest reliability of the Student Laptop Use and Musculoskeletal Posture (SLUMP) questionnaire among undergraduate University students. PARTICIPANTS: We invited 179 undergraduate students from two Health Sciences courses at the University of Ontario Institute of Technology to participate in the study in October 2015. METHODS: We conducted a test-retest reliability study. The SLUMP questionnaire, which includes 51 questions, was administered twice at a seven-day interval. We used weighted Kappa statistics to calculate test-retest reliability. RESULTS: Ninety-one students completed the study. 72.5% of the 51 questions achieved a Kw≥0.60 with 29.4% of questions achieving a Kw≥0.80. The reliability was similar for males and females. CONCLUSION: The SLUMP offers a promising method to measure biomechanical issues during laptop use among University students.